2011
DOI: 10.1159/000320711
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer: The Role of Pancreatic Stellate Cells in Tumor Progression

Abstract: Pancreatic ductal adenocarcinoma is an aggressive and highly lethal disease frequently characterized by a dense stromal or desmoplastic response. Accumulating evidence exists that tumor desmoplasia plays a central role in disease progression and that e.g. activated pancreatic stellate cells (PSCs) are responsible for the excess matrix production. The mechanisms underlying the tumor versus stroma interplay are complex. Pancreatic cancer cells release mitogenic and fibrogenic stimulants, such as transforming gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 61 publications
2
74
0
Order By: Relevance
“…CAFs secrete factors such as EGF, IGF-1, PDGF, FGF, MMP, and type I collagen that favor malignant progression [49][50][51], which lead to the deposition of the ECM, the promotion of angiogenesis and the EMT, and the enhancement of proliferation, immunotolerance, and resistance to chemotherapy (Figure 2) [52,53]. These CAF functions play important roles in cancer progression and promote tumor cell invasion and metastasis.…”
Section: Cancer-associated Fibroblasts (Cafs) In the Microenvironmentmentioning
confidence: 99%
“…CAFs secrete factors such as EGF, IGF-1, PDGF, FGF, MMP, and type I collagen that favor malignant progression [49][50][51], which lead to the deposition of the ECM, the promotion of angiogenesis and the EMT, and the enhancement of proliferation, immunotolerance, and resistance to chemotherapy (Figure 2) [52,53]. These CAF functions play important roles in cancer progression and promote tumor cell invasion and metastasis.…”
Section: Cancer-associated Fibroblasts (Cafs) In the Microenvironmentmentioning
confidence: 99%
“…Activated PSCs play key roles in the development of a fibrotic pancreatic stroma by increasing the synthesis of extracellular matrix proteins, such as collagen and enzymes responsible for matrix remodeling. Furthermore, several factors secreted from PSCs, such as platelet-derived growth factor (PDGF), galectin-1, stromal-derived factor 1, epidermal growth factor, insulinlike growth factor 1, and fibroblast growth factor, contribute to the increased invasiveness and proliferation of PDAC cells in vitro and in vivo [45,46]. PSCs have been shown to promote epithelial-tomesenchymal transition (EMT) [47,48] and a stem cell-like phenotype in pancreatic cancer cells [49], which are key features in enhancing tumorigenicity, cell migration, and resistance to chemotherapy.…”
Section: To Mediate Crosstalk Between Stromal Cells and Tumor Cellsmentioning
confidence: 99%
“…Based on the composition of the immune infiltrates surrounding PanINs, it has been shown that the stromal constituents surrounding PanINs form an inflammatory and immune suppressive environment thereby allowing the precursor lesions to escape immune surveillance [136]. The main pancreatic cancer-associated stromal fibroblasts, PSCs, are key players in the development of desmoplasia [137], and predominantly secrete gelatinases (MMP2, MMP9), which degrade the basement membrane collagen (type IV) and are associated with inflammation, fibrosis, angiogenesis, and cancer invasion. In various cancers including PDAC, basement membrane breaching, a critical step in cancer progression, brings malignant cells into direct contact with ECM proteins such as collagen type-1, thus supporting their growth, contributing to their chemo-resistance, and paving the way for invasion and metastasis.…”
Section: The Desmoplastic Stromamentioning
confidence: 99%